Interaction of preschool academic institution with a family raising a child with special needs (Pedagogy of Higher and Secondary Education, 2013)
Palasevich L. I. Interaction of preschool academic institution with a family raising a child with special needs.The article illuminates the main aspects of the upbringing children which have special needs in family conditions; focuses on the fact that the ability to follow the way in overcoming difficulties depends upon the parental ability to accept features in children’s development, to organize their own behavior in accordance to the children’s abilities and abilities to accept its needs; emphasizes the importance of a coordinated work of qualified specialists to support these families.
Keywords: children with special needs; family upbringing; pedagogical children support; personal development; creative self-actualization; pedagogue